Biocarriers for biofilm immobilization in wastewater treatments: a review - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; Vo, Dai-Viet N.; Tran, Ngoc Han (Springer Nature, 2020)
Biofilm carriers, named ‘biocarriers’, are solids that allow the good attachment of microbes during wastewater treatment. Biocarriers also act as redox mediators to speed up the biotransformation of contaminants in industrial effluents, yet it is challenging to choose a biocarrier material that achieves strong biofilm adhesion and high degradation rates. Here we review insoluble polymeric biocarriers with focus on selecting a biocarrier, biofilm growth, metabolic pathways, applications, surface modification, and composites. According to the efficiency to decrease the chemical oxygen demand, conventional and modified composite biocarriers are rated as following: polyvinyl alcohol > polyurethane > polyethylene > polypropylene, and polyvinyl alcohol > waste tire > polyurethane > polyethylene, respectively. We also discuss biological and physical fouling.